Knitwear : an introduction to contemporary design - Sissons, Juliana, 1959- (Bloomsbury Visual Arts, an imprint of Bloomsbury Publishing Plc, 2018)
Fully revised and updated, this new second edition of Knitwear provides an invaluable introduction to the use of knitwear in fashion design. The book delves into the characteristics and behavior of many varieties of yarn and fiber, from traditional to contemporary, providing easy-to-follow diagrams, practical examples, and rich illustrations throughout. Knitwear provides an insider's perspective into the knitwear industry and offers vital need-to-know information to readers on various career pathways, while highlighting contemporary machinery and tools available to knitwear designers today, demonstrating how to create knitting patterns, and laying out the basic techniques used on domestic machines. Interviews with international designers, operating at different levels within the industry, provide further insight into the business of knitwear, and how to get a good head-start into the industry. A must-have handbook for the knitwear designer, Knitwear is a beautiful and indispensable guide to this growing area of the fashion industry.
Keywords: Knit goods -- Design.; Fashion design.; elektronické knihy; electronic books